Teacher questioning strategies during the classroom interaction of eleventh grade at SMK muhammadiyah tolitoli - Firmansyah, Moh.; Risnawati, Risnawati (Universitas Madako Tolitoli, 2023)
This study aimed to determine the types of questions used by English teachers. The study was carried out in SMK Muhammadiyah Toli Toli. A qualitative descriptive design was employed to conduct this research. One English teacher who teaches in SMK Muhammadiyah Toli-Toli became the subject of this study. Observation and interview were the instruments used by the researcher to collect the data, which were then analyzed qualitatively. The researcher took the data in two meetings. After collecting the data, the data were analyzed based on Miles and Huberman, which consisted of three techniques: data reduction, data display, and conclusion. This study showed that, based on Richard and Lockhart's theory, the types of questions used by the English teacher include procedural questions (15 data) and convergent questions (14 data). The teacher frequently used procedural questions in a classroom. However, the researcher did not find that the teacher used different questions.